2018
DOI: 10.1111/nhs.12578
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Adherence to Standard Precautions Scale: A psychometric validation

Abstract: Despite the mandated use of standard precaution guidelines to limit infection transmission in health‐care settings, adherence by health‐care professionals is suboptimal. There is currently no psychometrically‐validated scale to assess influences on workers' adherence. After the data collection was conducted, Michinov et al. (2016) published a questionnaire to determine sociocognitive determinants of adherence to Standard Precautions. The aim of the present study was to develop and test the psychometric propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 37 publications
2
40
0
3
Order By: Relevance
“…When analyzing the answers of each of the CSPS-PB items for some items, compliance with SP for hand hygiene, use of PPE, bath after extensive spattering and needle repacking was unsatisfactory. These data corroborate with the literature, since [4][5][6][7][8] One of the concerns regarding the results presented is the hand hygiene between contacts with patients after removing the gloves, since Regulatory Standard 32 (NR-32) 14 states that the use of gloves does not replace the hand hygiene process, which should occur at least before and after the use of the same. Similar results were observed in a study that indicated adherence of 65.6% of the professionals to this practice, even though it was recognized as simple and important in the prevention and control of infections related to health care.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…When analyzing the answers of each of the CSPS-PB items for some items, compliance with SP for hand hygiene, use of PPE, bath after extensive spattering and needle repacking was unsatisfactory. These data corroborate with the literature, since [4][5][6][7][8] One of the concerns regarding the results presented is the hand hygiene between contacts with patients after removing the gloves, since Regulatory Standard 32 (NR-32) 14 states that the use of gloves does not replace the hand hygiene process, which should occur at least before and after the use of the same. Similar results were observed in a study that indicated adherence of 65.6% of the professionals to this practice, even though it was recognized as simple and important in the prevention and control of infections related to health care.…”
Section: Discussionsupporting
confidence: 87%
“…1,2 With a view to reducing accidents with biological material, it is important to adhere to preventive measures, such as Standard Precautions (SP). [3][4][5] SP have been established by the Centers for Disease Control and Prevention and adopted worldwide and are intended to protect health care professionals and ensure safe patient care, preventing infections in the provision of care. 4,5 Considering that behavioral factors such as decision-making not to use Personal Protective Equipment (PPE) or low perception of risk of exposure can influence compliance with SP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result that providing sufficient resources and training improved handwashing from 66 to 97% (Helms, Dorval, Laurent, & Winter, ) indicates that a safe environment, including resources such as nursing staff, material and equipment, and supportive hospital management, can result in increased nurse compliance with IPC practices. Although a nurse's individual knowledge and attitudes are important, a safe hospital environment must be established for effective IPC because behavioral changes are influenced by a combination of education, attitudes, and organizational changes (Bouchoucha & Moore, ; Valim et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A literatura evidencia que, ao realizar o encape ativo, as chances do profissional se acidentar aumentam em até 25 vezes (19) . Em muitos países, é exigido legalmente que as instituições de saúde disponibilizem aos profissionais de saúde agulhas com dispositivos de segurança, e estudos comprovam que tais dispositivos reduzem a ocorrência de acidentes perfurantes com agulhas e dispositivos intravenosos (20) .…”
Section: Discussionunclassified